A Study of International Criteria & Classifications Accredited in Assessing Universities - عمران ينل (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This piece of research aims at highlighting the reality of the Syrian universities and scientific research in the light of the international criteria for classifying universities. The researcher has followed the descriptive analytical methodology while collecting data since it is an appropriate one to pursue the research. Concerning the study tools, observing while reviewing universities assessment as adopted by world academic entities has been followed through surfing the web and monitoring the rank of the researched locations of the universities. Study findings reveal the absence of the private and governmental Syrian universities in these classifications. The researcher recommends the inevitability of changing the style of teaching in the Syrian Universities, next to the necessity of forming committees on the national level that is responsible for assessing the teaching programmers at the undergraduate and postgraduate levels; confirming the significance of adopting the policy of academic accreditation, and the necessity for the university library and the sources of paper and electronic data to be part of the curricula, concluding with encouraging companies to sponsor some of the scientific topics at the Syrian Universities.